Monitoring a Gall Midge Population on Russian Knapweed (Acroptilon repens). (December 2015) - Meyers, Kathleen; Pieropan, Nancy; Collier, Timothy
Abstract: This paper describes postrelease monitoring of a population of Jaapiella ivannikovi, a gall-forming midge that was introduced for biological control of Russian knapweed. In 2011 to 2013, from late May to early June through August, we monitored 100 permanent plots at one of the first release sites of J. ivannikovi in central Wyoming. Based on the phenology of gall formation, an appropriate window for collection of galls to distribute to new sites is from early to mid-June through early August. Although J. ivannikovi established successfully, 4 yr after release, the percentage of ramets that were galled remained low (1 to 2%), indicating that J. ivannikovi is not yet having a significant effect on Russian knapweed at the site.